COUNTRY OF ORIGIN AND PERCEIVED QUALITY IN MEDIATING THE INFLUENCE OF CONSUMER ETHNOCENTRISM ON PURCHASE INTENTION - Ardisa, Chintata; Rohman, Fatchur; Puspaningrum, Astrid (Universitas Brawijaya, Indonesia, 2022)
This study aims to determine and analyze the relationship between Consumer Ethnocentrism, Country of Origin, Purchase Intention, and Perceived Quality in local cosmetics of Indonesian products. This research will be conducted by the explanatory research method. The population of this study is women in Malang who already know the products of MAKEOVER but have never purchased the product. The sample from this study amounted to 186 respondents. This study, the number of variables studied as many as four variables, namely consumer ethnocentrism, country of origin, perceived quality, and purchase intention. This study was conducted to dispel the assumption that genuine local products, especially Indonesian cosmetics, are still often judged to be inferior to imported products. The data collection techniques in this study were conducted through questionnaires and documentation. The technique used in taking the sample was non-probability sampling using quota sampling from prospective consumers. Data analysis techniques used through validity tests use Confirmatory Factor Analysis (CFA) instrument validity tests, reliability tests, and Partial Least Square (PLS) approach with Smart PLS 3 software. The results showed that consumer ethnocentrism owned by women in Malang is a prospective consumer of local products has led to the interest in purchasing MAKEOVER products as opposed to imported cosmetic products, an exciting finding in this study because the high ethnocentric spirit does not make people want to buy local products, further findings that a good image of the country of origin is proven to influence the buying interest of prospective consumers and also proven to be a good antecedent between consumer ethnocentrism and purchase intention than perceived quality managed to be the primary mediation between consumer ethnocentrism and purchase intention in local products. Based on the result of this study, the company must compete with imported products by increasing the ethnocentrism campaign to its consumers so that it can create continuous purchase intentions in many ways.